The Effect of the Working Environment and the Work Period on the Performance of Bank BJB Employees Sukabumi Branch Office During the Covid-19 Pandemic - Arifin, Mohamad Zainal; Hermina, Nurul (Jurnal Maksipreneur, 2024)
The Covid-19 pandemic has put pressure on various aspects, including banking. One of them is Bank BJB, which has not been able to optimally develop the potential of its human resources in facing the pressure of the Covid-19 pandemic. The purpose of this study was to obtain the results of studies and analyses regarding the working environment and the work period or tenure in determining the performance of employees of Bank BJB Sukabumi Branch during the Covid-19. The research method used is the descriptive verification method, which produces a study of each variable and the results of the analysis of the relationship between variables that are suspected to have gaps. The sample in this study used the census method, all employees of Bank BJB Sukabumi Branch, 142 employees were the samples in this study. The analysis technique used in this research is the multiple regression hypothesis testing technique. The results showed that changes in employee performance at Bank BJB Sukabumi Branch Office were caused by the working environment and the work period. The finding of this research showed that the working environment and the work period have a significant effect on employee performance. In addition to these two variables, other factors can affect changes in employee performance that are not included in this research model.